Polymorphic variants involved in methylation regulation: a strategy to discover risk loci for pancreatic ductal adenocarcinoma - Corradi, Chiara; Lencioni, Giulia; Gentiluomo, Manuel; Felici, Alessio; Latiano, Anna; Kiudelis, Gediminas; van Eijck, Casper H J; Marta, Katalin; Lawlor, Rita T; Tavano, Francesca; Boggi, Ugo; Dijk, Frederike; et al. (Journal of medical genetics, 2023)
INTRODUCTION: Only a small number of risk factors for pancreatic ductal adenocarcinoma (PDAC) has been established. Several studies identified a role of epigenetics and of deregulation of DNA methylation. DNA methylation is variable across a lifetime and in different tissues; nevertheless, its levels can be regulated by genetic variants like methylation quantitative trait loci (mQTLs), which can be used as a surrogate. MATERIALS AND METHODS: We scanned the whole genome for mQTLs and performed an association study in 14 705 PDAC cases and 246 921 controls. The methylation data were obtained from whole blood and pancreatic cancer tissue through online databases. We used the Pancreatic Cancer Cohort Consortium and the Pancreatic Cancer Case-Control Consortium genome-wide association study (GWAS) data as discovery phase and the Pancreatic Disease Research consortium, the FinnGen project and the Japan Pancreatic Cancer Research consortium GWAS as replication phase. RESULTS: The C allele of 15q26.1-rs12905855 showed an association with a decreased risk of PDAC (OR=0.90, 95% CI 0.87 to 0.94, p=4.93×10-8 in the overall meta-analysis), reaching genome-level statistical significance. 15q26.1-rs12905855 decreases the methylation of a 'C-phosphate-G' (CpG) site located in the promoter region of the RCCD1 antisense (RCCD1-AS1) gene which, when expressed, decreases the expression of the RCC1 domain-containing (RCCD1) gene (part of a histone demethylase complex). Thus, it is possible that the rs12905855 C-allele has a protective role in PDAC development through an increase of RCCD1 gene expression, made possible by the inactivity of RCCD1-AS1. CONCLUSION: We identified a novel PDAC risk locus which modulates cancer risk by controlling gene expression through DNA methylation.
Keywords: DNA Methylation; Genetic Variation; Genetics; nádory slinivky břišní; celogenomová asociační studie; Humans; metylace DNA; Germ-Line Mutation; Molecular Epidemiology; Genome-Wide Association Study; Pancreatic Neoplasms; duktální karcinom slinivky břišní; lidé; Carcinoma, Pancreatic Ductal